Carbonate‐Grafted Polysilane as a New Additive for Elevated‐Temperature Lithium‐Ion Batteries. Issue 8 (17th May 2017) - Lu, Wei; Xiong, Shizhao; Pu, Wenjing; Xie, Kai; Zheng, Chunman
Abstract: New additives are required to meet the challenge for Li‐ion batteries working at elevated temperature. Here, we report ethylene‐carbonate‐grafted polysilane (PMSVC) as an additive of commercial carbonate‐based electrolytes. PMSVC is synthesized by using graft copolymerization of ethylene carbonate onto polymethylsilane within tetrahydrofuran solvent and azodiisobutyronitrile initiator. Fourier transform infrared spectroscopy and nuclear magnetic resonance spectroscopy show that the substitution degree of Si−H in final product is about 5 %. Electrochemical impedance spectra and charge−discharge tests of the cell with 0.5 wt % additive show that the film on a positive electrode was mainly formed during the initial five cycles at 0.2 C. The capacity retention of the cell with additive is about 87 % after 60 cycles at 60 °C, whereas the cell with baseline electrolyte is about 80 % under the same conditions. The results suggest that the addition of PMSVC is beneficial to the cycling stability of the cell at elevated temperature. X‐ray photoelectron spectroscopy analysis identified the compounds on a cycled LiCoO2 electrode, which are associated to the degradation, oxidation‐crosslink reaction, and unreacted groups of PMSVC. The mechanism to form the protective film on positive electrode is also further discussed in this work. Abstract : For your own protection : Ethylene‐carbonate‐grafted polysilane (PMSVC) is synthesized as an additive for commercial carbonate‐based electrolytes by using graft copolymerization of ethylene carbonate onto polymethylsilane within tetrahydrofuran solvent and an azodiisobutyronitrile initiator. The results suggest that the addition of PMSVC is beneficial to the cycling stability of the cell at elevated temperature. The mechanism of forming the protective film on a positive electrode is also further discussed.